Planning the evacuation of animals from large objects - Romuald Grocki (Scientific Journal of the Military University of Land Forces, 2019)
The article addresses the specificity and issues related to the evacua-tion of animals in an emergency situation. The author focused on the basic undertaking which is planning the evacuation of animals, mainly from large objects such as ZOOs, farms or studs. The article presents proposals for structures of evacuation teams, their competences and procedures. The attention was paid to the effectiveness of evacuation taking into account time relations, including distance during the occur-rence of an event. The author indicates important parts of the planning, namely the development of the right documentation and the verifica-tion carried out in terms of the feasibility of the implementation of the projects assumed in the plan. The article describes the structure con-cept of evacuation plans of animals from a large facility.